Pushing Differential Sensing Further: The Next Steps in Design and Analysis of Bio‐Inspired Cross‐Reactive Arrays. Issue 2 (26th January 2023) - Fargher, Hazel A.; d'Oelsnitz, Simon; Diaz, Daniel J.; Anslyn, Eric V.
Abstract: Differential sensing is a technique that uses an array of cross‐reactive receptors to create a unique fingerprint to detect analytes. Over the past two decades significant progress in the field has highlighted the power of this approach, enabling detection with commercially available or synthetically simple sensors, discrimination of structurally similar and challenging analytes, and low concentration detection. In this Concept paper, we briefly review developments in the field and highlight areas for future exploration. We believe there is still much room to grow, particularly in designing biosensor arrays, achieving simultaneous quantification of multiple analytes (i. e., multiplexing), and implementation of more advanced machine learning algorithms in array response analysis. Abstract : Differential sensing is a technique inspired by nature that identifies analytes from their unique response to cross‐reactive sensor arrays. In this Concept paper we highlight ways in which differential sensing may be advantageous over a traditional "lock‐and‐key" detection approach and identify areas in which we see significant potential for growth in this field.